Untargeted metabolomics yields insight into extramammary Paget’s disease mechanisms - Jiang, Long; Xu, Xiaoxiang; Yan, Guorong; Wu, Yuhao; Xi, Ningyuan; Lai, Yongxian; Zhang, Guolong; Liu, Yeqiang (Frontiers in Oncology, 2024)
Extramammary Paget's disease (EMPD) is a rare cutaneous malignancy, commonly affecting the external genitalia and perianal area of the elderly with unclear pathogenesis. Metabolomics provides a novel perspective for uncovering the metabolic mechanisms of a verity of cancers. Here, we explored the metabolome of EMPD using an untargeted strategy. Results showed that a total of 896 metabolites were identified and 87 metabolites including 37 up-regulated and 50 down-regulated significantly in EMPD were sought out. In the following feature selection analyses, four metabolites including cyclopentyl fentanyl-d5, LPI 17:0, guanosine-3',5'-cyclic monophosphate, kynurenine (KYN, high in EMPD) were identified by both random forest and support vector machine analyses. In order to further investigate the potential relationship between metabolites and gene expression, we re-analyzed the gene expression microarray data (GSE117285) using differential expression analysis and functional enrichments analyses. We found 1,079 dysfunctional genes including 646 up-regulated and 433 downregulated in EMPD. Specifically, the tryptophan-degrading enzyme including indoleamine-2,3dioxygenase-1 (IDO1) and tryptophan 2,3-dioxygenase (TDO2) were also increased. Generally, cancers exhibit a high expression of IDO1 and TDO2 to catabolize tryptophan, generating abundant KYN. Moreover, we also noticed the abnormal activation of sustaining proliferative signaling in EMPD. In conclusion, this study was the first to reveal the metabolome profile of EMPD. Our results demonstrate that IDO1/TDO2 initialized KYN metabolic pathway may play a vital role in the development and progression of EMPD, which may serve as a potential therapeutic target for treating EMPD.